Gangsters and G-Men on Screen: Crime Cinema Then and Now - Phillips, Gene D. (Rowman & Littlefield Publishers, 2014)
While the gangster film may have enjoyed its heyday in the 1930s and ’40s, it has remained a movie staple for almost as long as cinema has existed. From the early films of Humphrey Bogart, James Cagney, and Edward G. Robinson to modern versions like Bugsy, Public Enemies, and Gangster Squad, such films capture the brutality of mobs and their leaders. In Gangsters and G-Men on Screen: Crime Cinema Then and Now, Gene D. Phillips revisits some of the most popular and iconic representations of the genre. While this volume offers new perspectives on some established classics—usual suspects like Little Caesar, Bonnie and Clyde, and The Godfather Part II—Phillips also calls attention to some of the unheralded but no less worthy films and filmmakers that represent the genre. Expanding the viewer’s notion of what constitutes a gangster film, Phillips offers such unusual choices as You Only Live Once, Key Largo, The Lady from Shanghai, and even the 1949 version of The Great Gatsby. Also included in this examination are more recent ventures, such as modern classics The Grifters and Martin Scorsese’s The Departed. In his analyses, Phillips draws on a number of sources, including personal interviews with directors and other artists and technicians associated with the films he discusses. Of interest to film historians and scholars, Gangsters and G-Men on Screen will also appeal to anyone who wants to better understand the films that represent an important contribution to crime cinema.